South African Muslim Faith Healers Perceptions of Mental Illness: Understanding, Aetiology and Treatment - Ally, Yaseen (Journal of religion and health, 2008)
The important role that religious beliefs may have on perceptions of mental illness cannot be ignored. Many religions including Islam advocate witchcraft and spirit possessionall of which are thought to influence the behaviour of a person so as to resemble that of a mentally ill individual. Thus this research explored Muslim Faith Healers perceptions of mental and spiritual illness in terms of their understanding of the distinctions between the two, the aetiologies and the treatments thereof. Six Muslim Healers in the Johannesburg community were interviewed and thematic content analysis was used to analyse the data. From the results it is clear that the faith healers were aware of the distinction between mental and spiritual illnesses. It was also apparent that Islam has a clear taxonomy that distinguishes illness and the causes thereof. Treatments are then advised accordingly. Thus this paper argues that the predominant Western view of the aetiology and understanding of mental illness needs to acknowledge the various culturally inclined taxonomies of mental illness so as to better understand and aid clients.